The Urgency of Transformation of Islamic Education in the Era of Technology Disruption in the Post-Millennial Muslim Generation - Rahman Rasyidi; Fauzi Fauzi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The rapid development of information technology affects the world of education, including Islamic education. The responsibility of Islamic education in guiding humans in the face of the post-millennial era is an important thing to research. This study aims to identify the characteristics of the post-millennial Muslim generation in the future. Based on the literature study method, this study found that the post-millennial Muslim generation has different features from the previous generation. Based on these findings, it is urgent to transform Islamic education in the era of technological disruption in the post-millennial Muslim age.